2014
DOI: 10.17221/7655-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hen age, environmental temperature, and oviposition time on egg shell quality and egg shell and serum mineral contents in laying and broiler breeder hens

Abstract: ABSTRACT:The aim of the study was to evaluate egg shell quality characteristics, mineral content in the egg shell, and serum mineral concentration during the egg formation process as influenced by oviposition time and ambient temperature at the beginning and end of the laying cycle in laying hens and broiler breeders. Egg shell quality deteriorated significantly at the higher temperature and was lower in broiler breeders than in laying hens. The Ca (P = 0.047) and P (P = 0.018) contents of the egg shell were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 39 publications
2
9
0
1
Order By: Relevance
“…, Mg 3.32 g kg -1 and Zn 4.82 g kg -1 were observed in egg shell of Lohmann Brown laying hens (Tůmová et al, 2014).…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…, Mg 3.32 g kg -1 and Zn 4.82 g kg -1 were observed in egg shell of Lohmann Brown laying hens (Tůmová et al, 2014).…”
Section: Resultsmentioning
confidence: 81%
“…Park et al (2015) presented eggshell thickness of layers in the range from 0.37 to 0.40 mm. Tůmová et al (2014) indicated average eggshell thickness of Lohmann Brown laying hens 0.31 mm.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Feeding olive oil along with conjugated linoleic acid completely prevented changes in the mineral content of egg yolk and albumen. Average contents of Ca 344 g*kg were observed in egg shell of Lohmann Brown laying hens (Tůmová et al, 2014). Glisson and Walker (2010) reported that sodium, potassium and chlorides occurs for the most part as free minerals and other minerals are usually bound to proteins and phospholipids.…”
Section: Mineral Composition Of Egg Massmentioning
confidence: 99%
“…Present findings are not in agreement with those presented by Levkut et al (2011) who observed that chickens fed oregano oil supplemented diet had significantly higher serum magnesium concentration and slightly lower serum phosphorus level in comparison with birds from control group. Tůmová et al (2014) found average contents of serum Ca 4.18 mmol*l Enzymatic profile of blood of laying hens at the end of experiment is recorded in Table 5. AST, ALT, GGT, ALP and bilirubin of enzyme complex were observed in this trial.…”
Section: Blood Parameters Of Laying Hensmentioning
confidence: 99%